Childhood Active Transportation Determinants and their Effect on Adult Active Transportation (CADET) - Winslow, Daniel (My University, 2020)
Saline County Health Department in Salina (SCHD), KS is a unified City/County Health Department of a medium sized town in central Kansas. Saline County is home to 55,000 people, 47,000 of whom live in the county’s largest town and county seat, Salina. Salina’s demographic makeup places it in a typical bracket of Kansas counties, with very low racial diversity (<5% of each African American, Asian, American Indian and Native Alaskan or Pacific Islander), moderate representation of ethnically Hispanic individuals (11.4%) and an overwhelming majority of white individuals (90.2%). Up to 25% of Saline County can be classified as rural, and with medical and civic services centered around Salina’s downtown, challenges arise from the geographical dispersion of human services throughout town and county. SCHD is a moderately sized health department with 35 employees with 27 unique roles to play for county health. SCHD operates both as an administrative complex for child care licensing and emergency preparedness, as well as the site for the county’s Special Supplemental Nutrition Program for Women, Infants, and Children (WIC), a health clinic, home health, and maternal and child services including a Maternal & Child Health (MCH) Home Visitor program, Maternal & Infant (M&I) program, Kansas Special Health Care Needs (SHCN) program , and Becoming a Mom educational program. Salina maintains direct health services that shape its ability to take community spanning action through health policies and community programs. SCHD’s mission consists of managing community health through direct intervention, with educational and care programs available to pregnant women and children as well as the elderly. As part of the internship experience, I worked on a community resource map that encompassed community health care providers known to the State of Kansas, as well as community social service providers, such as food pantries, food banks, mental health care facilities and local support groups, such as churches, special interest groups and alliances for increased social and occupational access.
Keywords: Childhood Active Transportation Determinants; public health